Pidana Pengganti Denda Sebagai Bentuk Substitusi Pidana Dalam Pertanggungjawaban Pidana Koorporasi - Adriano Adriano (Universitas Muhammadiyah Surabaya, 2017)
There are differences of characteristics between natuurlijke person (man) with rechtspersoon (legal entity or corporation) even though they both constitute legal subjects, these differences result on assembling of the criminal. Criminal fines become a major staple for corporate criminal in its application can not stand alone but must be accompanied by a fine substitute criminal law enforcement in order to run run well. Jika denda tidak dibayar oleh natuurlijke person, then the person liable to imprisonment for a fine substitute. So what if it happened to the corporation, the rechtspersoon certainly can not be imposed imprisonment in substitute of fine. This article will answer in detail the intricacies associated with it and how criminal that should be applied to the corporation.